Hydrogen-atom tunneling through a very high barrier; spontaneous thiol → thione conversion in thiourea isolated in low-temperature Ar, Ne, H2 and D2 matrices. Issue 20 (10th May 2018) - Rostkowska, Hanna; Lapinski, Leszek; Nowak, Maciej J.
Abstract : Hydrogen-atom tunneling in thiourea involves breaking of the S–H chemical bond and the formation of a new N–H bond. Abstract : Spontaneous thiol → thione hydrogen-atom transfer has been investigated for molecules of thiourea trapped in Ar, Ne, normal-H2 (n-H2 ) and normal-D2 (n-D2 ) low-temperature matrices. The most stable thione isomer was the only form of the compound present in the matrices after their deposition. According to MP2/6-311++G(2d, p) calculations, the thiol tautomer should be higher in energy by 62.5 kJ mol −1 . This less stable thiol form of the compound was photochemically generated in a thione → thiol process, occurring upon UV irradiation of the matrix. Subsequently, a very slow spontaneous conversion of the thiol tautomer into the thione form was observed for the molecules isolated in Ar, Ne, n-H2 and n-D2 matrices kept at 3.5 K and in the dark. Since the thiol → thione transformation in thiourea is a process involving the dissociation of a chemical bond, the barrier for this hydrogen-atom transfer is very high (104–181 kJ mol −1 ). Crossing such a high potential-energy barrier at a temperature as low as 3.5 K, is possible only by hydrogen-atom tunneling. The experimentally measured time constants of this tunneling process: 52 h (Ar), 76 h (Ne), 94 h (n-H2 ) and 94 h (n-D2 ), do not differ much from one another. Hence, the dependence of the tunneling rate on the matrix environment is not drastic. The progress of the thiol → thione conversion was also monitored for Ar matrices at different temperature: 3.5 K, 9 K and 15 K. For this temperature range, the experiments revealed no detectable temperature dependence of the rate of the tunneling process.